IMPLIKASI APLIKASI SISTEM TEKNOLOGI INFORMASI DALAM PELAKSANAAN MANAJEMEN KUALITAS - Wibisono, Kunto (Universitas Muhammadiyah Surakarta, 2007)
The basic aim of this research is to examine the effect of information technologyon quality management. Sample of this research take place in 5 travel agentcompanies, 2 membership card companies, 4 education companies, and 3manufactures companies that used internet and website design for promoting theirproduct and services. In analyzing the data, researcher used paired sample t test.The result indicates there are significant relationship among used of informationtechnology and not used an information technology. Thatâs like a t heory said thatinformation technology gives a positive effect to company especially in qualitymanagement.The findings obtained in this research are expected could be used as asupplement reference for company, especially for specific company that willimplicated information technology.